The Role of Telemedicine in Digital Transformation Based on Patient Perceptions of Healthcare Accessibility and Efficiency - Blhaj, Khaled Mohamed Salem; Dhameria, Vita; Muazeib, Ahmed Ibrahim Maymoun (International Journal of Nursing Information, 2025)
The rapid adoption of telemedicine is transforming global healthcare systems by enhancing access and improving service efficiency, particularly in regions with limited healthcare infrastructure. However, the success of telemedicine depends not only on technology but also on how patients perceive and experience these services. This study aims to investigate the role of telemedicine in advancing digital transformation by analyzing patient perceptions of its impact on healthcare accessibility and service efficiency. A quantitative research method was applied using a structured questionnaire distributed to 150 patients who had used telemedicine services. Participants were selected from two developing countries, Libya and Indonesia, to provide cross-national perspectives. The collected data were analyzed using Structural Equation Modeling to evaluate the relationships among perceived accessibility, efficiency, and the contribution of telemedicine to digital transformation. The results show that patient perceptions play a significant role in determining the effectiveness of telemedicine in improving access and efficiency. Patients generally view telemedicine as a vital component of digital healthcare transformation, although variations exist due to differences in digital literacy and healthcare infrastructure. This study concludes that telemedicine can significantly support digital transformation if patient-centered design and localized implementation strategies are prioritized. The main contribution of this research is the empirical evidence highlighting the importance of patient perception in digital health adoption and offering insights for policymakers, healthcare providers, and technology developers to enhance telemedicine integration in diverse healthcare systems.